Does Streaming Esports Affect Players’ Behavior and Performance? - Matsui, Akira; Sapienza, Anna; Ferrara, Emilio (Games and culture, 2020)
In this work, we analyze what effect streaming gameplay on Twitch has on players’ in-game behavior and performance. We hypothesized that streaming can act as a form of implicit incentive to boost players’ performance and engagement. To test this hypothesis, we continuously collected data about all Twitch streams related to a popular Multiplayer Online Battle Arena (MOBA) game, League of Legends (LoL), and data of all LoL matches played during the same time frame, and cross-mapped the two data sets. We found that, counterintuitively, streaming significantly deteriorates players’ in-game performance: This may be due to the burden of carrying out two cognitively intensive activities at the same time, namely, playing the game and producing its commentary for streaming purposes. On the other hand, streaming increases engagement keeping players in significantly longer game sessions. We investigate these two effects further, to characterize how they vary upon individual characteristics.